基于风险自适应访问控制的健康医疗大数据隐私保护方法 (2023)
本发明公开了一种基于风险自适应访问控制的健康医疗大数据隐私保护方法，该方法只要分为三个模块：访问请求处理模块，权限管理模块及额度计算模块。其中，访问请求模块主要处理用户（医生）向管理系统提交访问请求后的主体判断流程，用户的访问请求予以通过将由访问请求模块判定；权限管理模块由原有框架中元素扩展而来，在原有权限的基础上，自适应地调整用户的访问权限，与访问请求处理模块共同解决了保护患者隐私的问题；额度计算模块则是计算由访问请求处理模型中发送过来的相应数据，具体为计算相对应访问请求在风险量化后的数值，本发明称这一数值为风险额度值。将计算过程分离出来，使得仅有访问请求处理这一模块决定访问响应时长，而该模块的内容为判定步骤，对计算资源的需求有限，从而解决了如何缩短大部分医生访问请求的响应时间的问题。 The invention discloses a health medical big data privacy protection method based on risk adaptive access control. The method only comprises three modules: an access request processing module, an authority management module and a limit calculation module. Wherein the access request module is mainly used for processing a subject judgment process after a user (doctor) submits an access request to the management system, and the access request of the user is judged by the access request module; the authority management module is formed by expanding elements in an original framework, the access authority of a user is adaptively adjusted on the basis of the original author